If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 6m = 12m + 48 Reorder the terms: 18 + 6m = 48 + 12m Solving 18 + 6m = 48 + 12m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12m' to each side of the equation. 18 + 6m + -12m = 48 + 12m + -12m Combine like terms: 6m + -12m = -6m 18 + -6m = 48 + 12m + -12m Combine like terms: 12m + -12m = 0 18 + -6m = 48 + 0 18 + -6m = 48 Add '-18' to each side of the equation. 18 + -18 + -6m = 48 + -18 Combine like terms: 18 + -18 = 0 0 + -6m = 48 + -18 -6m = 48 + -18 Combine like terms: 48 + -18 = 30 -6m = 30 Divide each side by '-6'. m = -5 Simplifying m = -5
| 12*6.8= | | 15y+60=30y+120 | | 2.1*6= | | 15y+40=30y+120 | | 18x-30=21x-14 | | 40-8h=4h-8 | | 5X(x+9)=6x+54 | | 24x+5=100 | | 9q-18=3q-36 | | -(-z-12)= | | 5x+1=3x-4 | | 6d-48=42-3d | | 11p-66=5p | | -(a-15)= | | 100+5p=60+2p | | x-2=2-3x | | 7k-49=22+2k | | (5x+2)(2x-5)=0 | | -(-9-4y)= | | g-1=5-1-9 | | -1(p+6)= | | 36y^2-1=15 | | 3.7q-1.9-3.4q=-0.7q-1.9 | | (1-11j)4= | | 3.7q-1.9q-3.4q=-0.7q-1.9 | | 7(11-n)= | | 0.3q-1.9=-0.7q-1.9 | | 12(4-8p)= | | 7+2(a-3)= -9 | | 17(2b+3)= | | 5m+5=7m-7 | | (6y-3)5= |